Analisis Perlakuan Pajak Penghasilan Bagi Wajib Pajak Wanita Kawin - ANGGARSARI, SUSI DIAH (UI Scholars Hub, 2011)
The research aims to analyze the income tax application for married women who fulfill their tax rights and obligations by themselves in the context of gender and taxable unit. The data in this qualitative research were collected through literature study and in-depth interview. In addition there is a comparison with Malaysia in terms of tax rights and obligations for married women taxpayers who fulfill their tax rights and obligations by themselves. The result of the research shows that there is limitation on the right of the married women to fulfill their tax rights and obligations by themselves, i.e. there is a restriction for the fulfillment of the tax rights of a married woman who becomes the head of the family. More over, in practice, the rule concerning the married women taxpayers who have to fulfill their income tax by themselves still sets problems for both the taxpayers and tax-officers. Therefore we need a socialization process in order to make known the stipulations concerning married women who have to fulfill their tax rights and obligations by themselves.